AN ANALYSIS OF PHONEMIC AND GRAPHEMIC CHANGES OF ENGLISH LOANWORDS IN BAHASA INDONESIA APPEARING IN MAGAZINE ENTITLED “CHIP” - Juliawan, M.D. (International Journal of Language and Literature, 2017)
This research aimed to describe the phonemic and graphemic changes of English loanwords in Bahasa Indonesia appearing in magazine entitled ‘CHIP’. The subjects of this research were the writers/editors of each articles of CHIP magazine. The objects of this research were English loanwords in Indonesian appearing in CHIP magazine ranging from 2013 to 2015 edition plus with the special edition of CHIP. The data were collected by reading and giving a mark to each borrowing words found or spotted in technology magazine (CHIP) through the process of reading. This study was a descriptive qualitative research which applying interactive data anaylisis model in analyzing the collected data. The results of this study show there are 12 processes of phonemic changes specifically for consonants. There are 8 processes of phoneme shift, 2 processes of phoneme split, and 2 processes of apocope. There are 10 phonemic changes of vowel: 1 process of phoneme split, 2 processes of phoneme shift, 2 processes of phoneme merger and 5 processes of paragoge. There are two types of graphemic changes found, namely pure phonological adaptation and syllabic adaptation. In the syllabic adaptation process, there are four processes of graphemic change, namely (1) double consonants become single consonant, (2) double vowels become single vowel, (3) monosyllable become disyllable, and (4) consonant inhibitory at the end of consonant clusters is disappear.